Sur la « révolution » de 1808-1814 - Claude Morange (Mélanges de la Casa de Velázquez, 2008)
The period 1808-1814 has been the object of manifold and sometimes conflicting interpretations. In this context, the author proposes to examine the extent to which the process, which was very much conditioned by the war, internal contradictions and the flow of events, can be described as revolutionary. In those years Spain experienced something more than a simple victory over Napoleon: namely, a break with the Ancien Regime which ushered in a vast programme of reforms. But the process was neither linear, progressive nor cohesive, and it would be an over-simplification to describe it as largely revolutionary without taking into account the chronology, the diversity of regional situations and the dialectical bond linking revolution and counter-revolution.